Hepatic artery embolization for treating giant hemangioma of liver: an experience from a tertiary level hospital in India - Bhuva, Dharmik; Agrawal, Manish; Rathod, Jawahar; Kamble, Chandrakant; Biswas, Anup (International Journal of Research in Medical Sciences, 2017)
Background: Transcatheter hepatic artery embolization (TAE) is a minimally invasive procedure. This study aimed to assess radiological features of giant haemangioma of liver on untrasonography, contrast enhanced tomography, magnetic resonance imaging and digital subtraction angiography, to assess the safety, feasibility and efficacy of transcatheter arterial embolization of hepatic artery in giant liver haemangioma. Methods: This prospective study was conducted in the Interventional Radiology Department, Government Medical College Nagpur from September 2013 till August 2015. Patients were enrolled who were diagnosed with liver hemangioma after obtaining an informed consent. Patients underwent routine investigations and imaging modalities like ultrasonography, contrast enhanced computed tomography. Patients were followed up at 3 months and 9 months. Results: During the study period, 28 patients were enrolled, 9 males, most common age group being 31-50 years. Abdominal discomfort was the most common symptom. Majority of the lesions were hyperechoic and not vascular. On CECT most of the lesions appeared progressive centripetal. On DSA heaptic artery was the most common source of vascular supple. Statistically significant change in size of the lesion was observed on either lobe when imaged via USG or CECT. No long term complications were seen in majority of the patients. Conclusions: This study shows that TAE in Giant Hepatic Haemangiomas is safe, feasible, efficient, and minimally invasive with good patient acceptance, minimal complications and no mortality.